Consumer Perceptions, Behaviors, and Knowledge of Food Waste in a Rural American State - Ahmed, Selena; Stewart, Alyssa; Smith, Erin; Warne, Teresa; Byker Shanks, Carmen (Frontiers in Sustainable Food Systems, 2021)
Understanding consumer knowledge, attitudes, and behaviors towards food waste is critical for informing evidence-based programs to advance sustainable food systems. A lack of knowledge regarding consumer food waste at the local level limits the ability to inform place-based solutions that are locally relevant. We administered an online survey to examine consumer perceptions, behaviors, and knowledge of food waste at the household level in Montana, a rural state in the United States. The majority of surveyed participants (58%) reported that they waste 10% or less of procured food. Almost half the participants (48%) are willing to take additional action to reduce food waste. Social factors including guilt and setting a good example were found to be greater motivators for reducing food waste compared to economic and environmental factors. Most survey participants (80%) perceive it would not be difficult to notably reduce their household` food waste. Overall, participants’ reporting of their household’s food waste quantity is lower than national quantities while their willingness to reduce food waste was higher than findings from a national survey. This study highlights the need for place-based solutions that are locally relevant to reduce household food waste towards enhancing the sustainability of food systems for supporting planetary health.